2020
DOI: 10.1002/brb3.1832
|View full text |Cite
|
Sign up to set email alerts
|

Apoaequorin differentially modulates fear memory in adult and aged rats

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 102 publications
(156 reference statements)
0
2
1
Order By: Relevance
“…However, these effects are difficult to disentangle from the age-related increase in threat memory generalization demonstrated here and elsewhere (Feiro and Gould 2005, Shoji et al 2016, Yanai and Endo 2021, in addition to previously reported age-related deficits in context discrimination (Corcoran et al 2002, Hernandez et al 2022. Contrary to some (Stoehr and Wenk 1995, Oler and Markus 1998, Doyere et al 2000, Corcoran et al 2002, Gemma et al 2005, Moyer and Brown 2006, Fukushima et al 2008, Kaczorowski and Disterhoft 2009, Villeda et al 2011, Ehlers et al 2020, Yanai and Endo 2021, Hernandez et al 2022 but not all (Gould and Feiro 2005, Aziz et al 2019, Shoji and Miyakawa 2019 previous reports, we find no effects of age on contextual threat memory. However, in our study, context was conditioned in the background rather than foreground (Huckleberry et al 2016).…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…However, these effects are difficult to disentangle from the age-related increase in threat memory generalization demonstrated here and elsewhere (Feiro and Gould 2005, Shoji et al 2016, Yanai and Endo 2021, in addition to previously reported age-related deficits in context discrimination (Corcoran et al 2002, Hernandez et al 2022. Contrary to some (Stoehr and Wenk 1995, Oler and Markus 1998, Doyere et al 2000, Corcoran et al 2002, Gemma et al 2005, Moyer and Brown 2006, Fukushima et al 2008, Kaczorowski and Disterhoft 2009, Villeda et al 2011, Ehlers et al 2020, Yanai and Endo 2021, Hernandez et al 2022 but not all (Gould and Feiro 2005, Aziz et al 2019, Shoji and Miyakawa 2019 previous reports, we find no effects of age on contextual threat memory. However, in our study, context was conditioned in the background rather than foreground (Huckleberry et al 2016).…”
Section: Discussioncontrasting
confidence: 76%
“…Sex differences have been reported in anxiety-like behavior (Kokras and Dalla 2014), social investigation (Tejada and Rissman 2012), and emotional memory (Bauer 2023), among other behaviors. Across aging, rodent models demonstrate increases in anxiety-like behavior (Darwish et al 2001, Boguszewski and Zagrodzka 2002, Narita et al 2006, Turner et al 2012, Stanojlovic et al 2019, Li et al 2020, Hirano et al 2021, Yanai and Endo 2021, decreases in social behaviors (Guan and Dluzen 1994, Boguszewski and Zagrodzka 2002, Salchner et al 2004, Hunt et al 2011, Perkins et al 2016, Shoji et al 2016, Gerasimenko et al 2020, and impairments in emotional memory processes (Stoehr and Wenk 1995, Oler and Markus 1998, Houston et al 1999, Doyere et al 2000, Corcoran et al 2002, Liu et al 2003, Gemma et al 2005, Moyer and Brown 2006, Fukushima et al 2008, Kaczorowski and Disterhoft 2009, Peleg et al 2010, Villeda et al 2011, Shoji et al 2016, Aziz et al 2019, Shoji and Miyakawa 2019, Ehlers et al 2020, Yanai and Endo 2021, Hernandez et al 2022. Despite these clear effects of age and sex on socioemotional behaviors, shockingly few studies have directly compared these behaviors in males and females across aging.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the calexcitin injection into photoreceptors of gastropods was capable to reproduce the electrophysiological effects of learning. In the last decade different groups showed that photoprotein aequorin may also administer the cognitive function [4]. Despite a very low sequence homology (18 %), Ca 2+ -loaded conformational state of apo-aequorin and calexcitin reveal a very high structural similarity of their main chains (RMSD 3.6 Å).…”
mentioning
confidence: 99%